Characterization of the Inhibitory Effect of Vascular Endothelium on Agonist-Induced Vasoconstriction in Rat Mesenteric Resistance Arteries - Xin Jin; Yukiko Satoh-Otonashi; Yoshito Zamami; Toshihiro Koyama; Pengyuan Sun; Yoshihisa Kitamura; Hiromu Kawasaki (Elsevier, 2008)
Vascular endothelium regulates vascular tone by releasing endothelium-derived vasoactive substances. We performed this study to characterize the inhibitory effect of the endothelium on vasoconstrictor stimuli in rat mesenteric vascular beds. Changes in perfusion pressure induced by continuous perfusion of Krebs solution containing methoxamine (α1-adrenoceptor agonist) or high KCl were measured over 180 min. In preparations with intact endothelium, methoxamine-induced vasoconstriction was time-dependently decreased to cause 60% - 80% reduction of the initial vasoconstriction level, while no reduction was observed in high-KCl-induced vasoconstriction. Endothelium removal significantly blunted the time-dependent reduction of methoxamine-induced vasoconstriction without affecting high-KCl-induced vasoconstriction. Neither a nitric oxide synthase inhibitor (L-NAME) nor indomethacin (cyclooxygenase inhibitor) altered the time-dependent reduction of vasoconstriction. High KCl, K+-channel inhibitors tetraethylammonium and apamin plus charybdotoxin, and 18α-glycyrrhetinic acid (18α-GA, a gap-junction inhibitor) significantly inhibited the time-dependent reduction of methoxamine-induced vasoconstriction. In preconstricted preparations, bolus injection of acetylcholine and Ca2+-ionophore A23187 (A23187) evoked a sharp vasodilation, which was inhibited by endothelium removal, high KCl and tetraethylammonium, but not indomethacin, L-NAME, or 18α-GA. However, 18α-GA plus L-NAME inhibited vasodilation induced by A23187, but not acetylcholine. These findings suggest that endothelium-derived hyperpolarizing factor (EDHF) via gap junctions mainly counteracts vasoconstriction induced by methoxamine in mesenteric resistance arteries. Keywords:: methoxamine-induced vasoconstriction, endothelium-derived hyperpolarizing factor, rat mesenteric resistance artery, gap junction